Investigating the Landscape of Programmed Death-Ligand 1 (PD-L1) in Thymic Tumors: Implications for Histopathological Classification and Staging - Rio Hendra; Noza Hilbertina; Henny Mulyani; Tofrizal; Afriani; Husna Yetti (HM Publisher, 2025)
Background: Thymic epithelial tumors (TETs) are uncommon malignancies originating in the mediastinum, characterized by considerable histopathological diversity and variable clinical trajectories. Programmed Death-Ligand 1 (PD-L1), an immune checkpoint protein, is implicated in mechanisms of tumor immune evasion. This study aimed to investigate the correlation between PD-L1 immunoexpression and distinct histopathological types, as well as the Masaoka-Koga stage, in TETs. Methods: This cross-sectional investigation analyzed 29 archival cases of TETs diagnosed between January 2019 and December 2024 at the Anatomical Pathology Laboratory of Dr. M. Djamil General Hospital Padang. Samples were procured via consecutive sampling from formalin-fixed paraffin-embedded (FFPE) tumor tissues. Histopathological classification was reassessed according to the WHO 2021 criteria. PD-L1 expression was evaluated immunohistochemically and quantified using the Tumor Proportion Score (TPS). Masaoka-Koga staging was determined from clinical records. Statistical analysis of correlations was performed using the Chi-square test. Results: PD-L1 immunoexpression was detected in the preponderance of cases. Low positive PD-L1 expression (TPS 1-49%) was observed in 82.8% of TETs, while high positive expression (TPS ≥50%) was noted in 10.3%. Thymic carcinoma constituted the most prevalent histopathological category (51.7%), and the majority of patients (91.7%) presented at an advanced Masaoka-Koga stage. Statistical analysis did not demonstrate a significant correlation between PD-L1 expression levels and histopathological type (p=0.195). Furthermore, no significant association was identified between PD-L1 expression and Masaoka-Koga stage (p=0.800). Conclusion: This study indicated that while PD-L1 is frequently expressed in TETs within this cohort, its expression level did not exhibit a significant correlation with specific histopathological subtypes or the Masaoka-Koga clinical stage. Further investigations incorporating larger sample sizes are warranted to delineate the precise role of PD-L1 within the complex biological spectrum of thymic neoplasms.